Literature Review : Komposisi Lambung Famili Scombridae di Perairan Indonesia - Anggi Pratiwi; Cut Syifa Almira; Firdus Firdus; Muhammad Nasir; Zainal Abidin Muchlisin (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
The Scombridae family is a family of fish species such as tuna, skipjack, mackerel, mackerel, mackerel and tuna. Fish from the Scombridae family can be categorized into carnivorous and omnivorous fish depending on the type of food consumed. The purpose of this paper is to determine the gastric composition of the Scombridae family in Indonesian waters. This research uses the literature review method and the articles selected as references are sourced from scientific journals, namely google scholar. The results showed that the stomach composition of skipjack, yellowfin tuna, tuna and gray tuna were fish, squid and Crustacea, while the stomach composition of male mackerel and female mackerel were phytoplankton, zooplankton, Cepopoda, Crustacae, Chepalopoda, Bivalvia, fish and squid.